CM-scale air turbine and generator for energy harvesting from low-speed flows - Bansal, A; Howey, D; Holmes, A (IEEE, 2009)
We have developed a 2-cm-diameter, shrouded wind turbine with an integrated axial flux permanent magnet generator. The device was fabricated using a combination of rapid prototyping, traditional machining and flexible printed circuit board technology, and employs jewel bearings for low friction. Wind tunnel tests have been performed on prototypes with 6 and 12 blades. The 12-blade design achieves a generator output power of 4.3 mW at a tunnel flow speed of 10 ms, and will operate at flow speeds down to 4.5 ms . With such a low drop-out speed the device could be used as an energy harvester in duct sensing applications.